Evaluating the Growth of MSMEs within Industrial Infrastructures: Insights from Assam, India - Das, Daisy; Ch Das, Tilak (International Journal of Economics and Financial Issues, 2025)
This study evaluates the performance and growth patterns of Micro-Small and Medium enterprises (MSMEs) within industrial infrastructures in Assam, focusing on the Kamrup and Kamrup Metro districts. Through a detailed analysis of investment, employment, profitability, and sales trends from 2017 to 2022, the research identifies both opportunities and challenges faced by these enterprises. The findings reveal a decline in employment, particularly among male and unskilled workers, reflecting structural issues in the workforce. Investment in capital assets such as plant and machinery has decreased, while working capital investments remain stable, indicating a focus on liquidity. Profitability shows stable gross profits but shrinking net margins, pointing to rising operational costs. While domestic sales have grown steadily, the absence of international sales highlights missed export opportunities. The role of industrial infrastructure in supporting MSME growth is evident through access to essential services, proximity to markets, and logistical advantages. However, maintenance issues, policy inefficiencies, and limited technological support hinder long-term growth. The study offers policy recommendations aimed at improving infrastructure quality, expanding market access, and promoting sustainable business practices, contributing to the success and sustainability of MSMEs.